MANDATORY LANDOWNER CONSENT AS A METHOD OF CONTROLLING WILD TURKEY HUNTER DENSITY AND HUNTER SUCCESS RATES - Brian K. Miller; Dale W. May (Wildlife Society Bulletin)
Abstract: Ninety‐five percent of Connecticut's 12,973.3 km2 is in private ownership. The human population density of about 239/km2 places a heavy demand by wild turkey (Meleagris gallopavo silvestris) hunters on the open space in private ownership and on the 344.5 km2 of state land available for hunting. In an effort to keep private lands open to wild turkey hunting, we instituted a system of written mandatory landowner consent for turkey hunting at the onset of Connecticut's first modern‐day turkey hunting season in 1981. After 9 years, the number of landowners permitting wild turkey hunting has increased by 308%. This trend is partially attributable to the expansion of huntable range since 1981. However, private land area open to turkey hunting has increased by 37.9% since 1987 while total huntable range remained stable. This landowner consent system has also controlled hunter density on private lands (1.5‐2.3 hunters/km2) keeping it lower than on state lands (2.2‐3.2 hunters/km2) where hunter density was controlled by lottery selection during the 1981‐1987 period. Hunter success rates on private land ranged from 13.1 to 25.5%, about 3‐5 times higher than on state land (2.4‐6.4%).